Reliability: an introduction. - Bonzio, Stefano; Landes, Jürgen; Osimani, Barbara (Synthese)
Formal epistemology and the replication crisis There are two main formal models of source reliability and confirmation in the current literature on Bayesian epistemology Bovens and Hartmann ([2]); Olsson ([29]). Tolly draws on the notion of multi-type evidential reliabilism (MTE) and the standard toolset of counterfactual semantics, in order to identify the truth conditions for a learning process to be defined as reliable: knowledge-enabling reliability requires a process token to be reliable with respect to multiple content-evidence pairs (i.e., the propositional content of the knowledge items, and the related evidential basis), each with varying degrees of specificity. Barbara Osimani is the PI of the European Research Council-founded project PhilPharm and gratefully acknowledges being fully funded by the project (Grant 639276). While we were working on this question using a formal epistemology approach Landes and Osimani ([24]); De Pretis et al. ([8]); Osimani and Landes ([32]); Osimani ([31]), we realised that the width of current active interests in the notion of reliability was much broader than we initially thought.